ANALISIS PENERAPAN ACTIVITY BASED COSTING TERHADAP TINGKAT AKURASI PERHITUNGAN HARGA POKOK PRODUKSI PADA PT TONGGAK AMPUH BATURAJA DI KABUPATEN OGAN KOMERING ULU - Pratama, Aldi Yudha; Anwar, Yuniarti; Wiralaga, Harby R (STIE DWI SAKTI BATURAJA, 2023)
This research is entitled Analysis of the Application of Activity Based Costing to the Accuracy of Calculation of Cost of Production at PT Tonggak Ampuh Baturaja in Ogan Komering Ulu Regency. The formulation of the problem in this study is how to apply activity based costing to the level of accuracy in calculating the cost of production at PT Tonggak Ampuh Baturaja in Ogan Komering Ulu Regency. In this study using descriptive methods with data collection techniques by means of observation, interviews, documentation and literature study. The analysis technique used in this research is quantitative data analysis technique using activity based costing method. Based on the results of the research, the calculation of the cost of goods sold by the company does not explain in detail the imposition of the cost of production. Factory overhead costs are not allocated to each product in real terms but only use one cost driver. If it is seen from the cost of production which is calculated based on the activity based costing method and the company's method in 2022, the product has a cost difference from the company's method. This is because the charging of overhead costs in the activity based costing method is charged according to the activities consumed by the product, while the company's method of charging overhead costs is proportional to the number of units produced